2019
DOI: 10.1590/2175-8239-jbn-2018-0127
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Epidemiology in pediatrics

Abstract: We performed a search in the MEDLINE database using the MeSH term: "Acute Kidney Injury", selecting the subtopic "Epidemiology", and applying age and year of publication filters. We also searched for the terms: "acute renal failure" and "epidemiology" "acute tubular necrosis" and "epidemiology" in the title and summary fields with the same filters. In a second search, we searched in the LILACS database, with the terms: "acute renal injury", or "acute renal failure" or "acute kidney injury" and the age filter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 56 publications
0
14
1
2
Order By: Relevance
“…Pediatric AKI studies have typically focused on critically ill populations or those children requiring dialysis, thus making our analysis unique (8,(22)(23)(24)(25)(26). Additionally, large cross-sectional pediatric cohort studies have investigated inpatient populations and reported sepsis/shock, respiratory failure, liver or heart disease, bone marrow transplant, hemolytic-uremic syndrome, and nephrotoxic medications as the most common causes of pediatric AKI (25,(27)(28)(29). While urinary stones are noted in multiple studies, they are not considered a major cause of pediatric AKI; however, Jamal et al found that urinary stones accounted for 30% of AKI in a single-center Pakistani cohort (12).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric AKI studies have typically focused on critically ill populations or those children requiring dialysis, thus making our analysis unique (8,(22)(23)(24)(25)(26). Additionally, large cross-sectional pediatric cohort studies have investigated inpatient populations and reported sepsis/shock, respiratory failure, liver or heart disease, bone marrow transplant, hemolytic-uremic syndrome, and nephrotoxic medications as the most common causes of pediatric AKI (25,(27)(28)(29). While urinary stones are noted in multiple studies, they are not considered a major cause of pediatric AKI; however, Jamal et al found that urinary stones accounted for 30% of AKI in a single-center Pakistani cohort (12).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is relevant in the context of critically ill children because drug-induced renal dysfunction is potentially reversible. ( 2 )…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a complication often found in patients admitted to the pediatric intensive care unit (ICU) and is characterized by a reduced glomerular filtration rate and/or urine output. ( 1 , 2 ) The main complications related to this disorder are increased fluid overload, reduced excretion of nitrogen compounds, and fluid and electrolyte and acid-base disorders. In addition, patients have longer hospital stays and a higher risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a sudden decline in renal function that is characterized by retention of nitrogenous waste products [ 1 ]. Globally, it is one of the leading causes of childhood death, with varying incidence, etiologies, and outcomes [ 2 ]. The pooled global incidence of pediatric AKI is estimated at 33.7% (95% confidence interval [CI], 26.9 to 41.3) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%